Wireless local area networks: a study of bit error rate (BER), modulation type and signal speed / Anitah Apolonius - Apolonius, Anitah (1997)
This project covers two main parts. The first part covers an in-depth study on wireless local area networks (WLANs) which covers its benefits, applications, protocols, adaptations and feasibiüty. The second part of the project is a study of a wireless point-to-point communication LAN network using two sets of walkie-talkie as a mode to transmit the data wireiessly from a personal computer to another via modems. The performance of the transmission is studied in terms of bit error rate (BER), modulation type and signal speed.